Unusual presentation of a giant benign inflammatory polyp in the upper esophagus. (2015) - Rawashdeh, Badi; Meyer, Mark; Gill, Jasmine; Moslemi, Mohammad; Kim, Samuel
Highlights: This case report highlights a rare type of esophageal polyps (inflammatory fibroid polyp). This case report presents a giant esophageal inflammatory fibroid polyp. This case report represents the second reported case for giant inflammatory fibroid polyps that is originated from the upper esophagus. Abstract: Introduction: Benign inflammatory fibroid polyps (IFP) are rare submucosal tumors of the upper gastrointestinal tract. Rarely, they can develop in the esophagus, usually in the lower third. There are only 12 cases of giant IFP of the esophagus reported in literature and little is known about their origin, biological behavior and operative management. We present a patient with a giant benign IFP of the esophagus that originated from the upper esophagus. Case presentation: The patient is a 59-year-old male who presented with dysphagia. Upper endoscopy and esophagram revealed a giant intraluminal esophageal mass with a pedicle in the upper esophagus. Resection of this mass was performed through a left cervical esophagotomy. Pathology confirmed IFP, On 2 year follow up, there was no recurrence of the mass. Discussion: A giant IFP is defined as an IFP greater than 4 cm, commonly present in the distal esophagus. Pathology usually reveals vascularized fibrous stroma with elements of inflammatory infiltrate. This mass is slow-growing and asymptomatic until it grows to a large size. Common diagnostic studies include barium esophagram, upper endoscopy, and CT imaging. A key pre-operative work-up is to identify the location of the pedicle to plan out surgical approach and to avoid injuring the rich blood supply thus preventing a life threatening hemorrhage during the operation. Conclusion: Giant IFPs are infrequent in clinical practice. Resection is indicated and usually performed by a surgical intervention or endoscopic removal. The pathogenesis of these polyps remains poorly understood due to the rarity of these lesions.